Implementation of Civics Education Learning on the Topic of Respecting Cultural and Religious Differences in Daily Life for 6th Grade Elementary/Islamic Elementary School Students. - Farida Catur Wahyu Anggriyani; Sugianor; Farhan (Penerbit Hellow Pustaka, 2025)
Citizenship Education (PKN) in elementary schools has an important role in shaping students' character as citizens who have social awareness and tolerance for cultural and religious differences. This article examines the implementation of PKN learning material